An Investigation of a Video-Based Preference Assessment of Social Interactions. Issue 5 (September 2018) - Wolfe, Katie; Kunnavatana, S. Shanun; Shoemaker, Adrianna M.
We examined the use of a paired-stimulus, video-based preference assessment (VPA) to identify high- and low-preference social interactions for three children with autism spectrum disorder. We conducted two VPAs with each participant: one with access to the interaction contingent on each selection and one without access. We also conducted a concurrent-operant reinforcer assessment to evaluate the accuracy of the VPAs in identifying reinforcers. For two participants, the VPAs corresponded strongly and the results of the reinforcer assessment suggest that the high-preference interaction produced more of the target response than the low-preference interaction. For the other participant, the VPAs identified different high- and low-preference interactions, and the results of the reinforcer assessment suggest that the VPA without access may have been more accurate in identifying a reinforcer.